Bosnia and Herzegovina : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that after several years of double-digit growth rates, real GDP for Bosnia and Herzegovina increased by about 5.5 percent in 2001. The growth slowdown was particularly marked in the Republika Srpska, where output grew by just 2 percent. The slowdown-which is partly owing to lower aid-financed reconstruction spending-marks the end of the post-war economic rebound. Industrial production is still less than half its pre-war level and measured unemployment remains high at 40 percent.